Modelling for secondary mathematics teacher: insight from expert - Riyan, Hidayat; Ahmad Fauzi, Mohd Ayub; Mohd Afifi bin Bahurudin, Setambah; Nurul Hijja, Mazlan; Kayshalini S, Balachandran (2025)
There has been significant research interest over the years in evaluating instructors' self-efficacy. Teacher self-efficacy reflects the confidence teachers have in their capacity to positively impact student achievement. This study seeks to develop a reliable and valid scale specifically designed to measure the modelling self-efficacy of mathematics teachers (MSES). We chose a mixed methods approach to harness the benefits of both qualitative and quantitative research techniques. The process began with collecting qualitative data through expert interviews, followed by the acquisition of quantitative data through a survey. The qualitative data will be analyzed using thematic analysis, while Rasch analysis will be applied to the quantitative data. The psychometric properties of the MSES will be evaluated using Winstep software. The qualitative findings identified six key components: modelling cycle knowledge efficacy, modelling task knowledge efficacy, pedagogical efficacy, assessment efficacy, and technology software efficacy. The instrument demonstrated excellent person reliability (.99) and separation (8.70). A floor effect was observed for 1 person (.4%). All items showed a satisfactory fit to the Rasch model. The raw variance explained by the measures was 73.6% (with 67.3% explained by persons and 6.2% by items). However, the instrument did not perform well in terms of item targeting. Person measures ranged from -8.78 to 5.48, with a mean (M) of 2.43, a standard deviation (SD) of 2.90, and a standard error (SE) of 0.1. The research suggests a pressing need for comprehensive reforms in curriculum design, professional development, assessment practices, and instructional strategies to improve the effectiveness of mathematical modeling instruction in Malaysia.